Polyimide gas separation membranes containing both fluorenyl cardo structures and troger's base (tb) motifs and methods of making the same

CN122912706APending Publication Date: 2026-10-16NORTHWESTERN POLYTECHNICAL UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611095451.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]目前高分子气体分离膜不仅长期面临“Trade-off”效应问题,导致气体渗透性与选择性难以兼得,限制了膜的综合分离效率

Benefits of technology

本发明从分子结构设计的角度出发,开发了一种将芴基Cardo结构、TB基元、短链烷基取代基一并引入PI分子主链的技术方法,并利用烷基在有氧条件下发生的热氧交联反应,进一步优化了链间堆积状态和膜孔结构,显著提升了PI薄膜的综合气体分离性能,超越了Robeson上限。本发明所制备的PI气体分离膜具备高渗透通量、高选择性、高强度以及抗塑化的优点。本发明提出的技术路线可为PI气体分离膜的分子结构设计、高效制备与分离性能优化提供多样化的设计思路,有助于推进PI气体分离膜在分离纯化领域的广泛应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912706A_ABST
    Figure CN122912706A_ABST
Patent Text Reader

Abstract

The application relates to a polyimide gas separation membrane containing a fluorenyl Cardo structure and a Tröger's Base (TB) base element simultaneously and a preparation method thereof, and the gas separation membrane is made of a gas separation membrane precursor containing a polyimide (PI) shown in formula (I) through thermal oxygen crosslinking. The fluorenyl Cardo structure, the TB base element and a short-chain alkyl substituent are introduced into a PI molecular main chain, and the thermal oxygen crosslinking reaction of the alkyl under an oxygen condition is utilized to further optimize the interchain stacking state and the membrane pore structure, and the comprehensive gas separation performance of the PI thin film is significantly improved, and the Robeson upper limit is exceeded. The application provides a diversified design idea for the molecular structure design, efficient preparation and separation performance optimization of the PI gas separation membrane, and helps to promote the wide application of the PI gas separation membrane in the separation and purification field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of gas separation and purification technology, specifically relating to a polyimide gas separation membrane whose molecular backbone includes a fluorene Cardo structure and a Tröger's Base (TB) motif, and its preparation method. Background Technology

[0002] The negative impacts of industrialization have led to a series of severe environmental problems, including frequent extreme weather events and global warming. Currently, reducing energy consumption and developing new-generation low-carbon and environmentally friendly technologies have become a global consensus among governments. In the chemical industry, separation processes account for approximately 50% of total energy consumption, making them a crucial component of chemical production. In recent years, with the introduction of the "dual-carbon" strategy, a large number of green and low-energy-consumption emerging separation technology industries have flourished. In the field of gas separation and purification, compared to traditional methods such as amine absorption, pressure swing adsorption, and cryogenic distillation, membrane separation technology, due to its advantages of not involving phase changes, low emissions, small footprint, and low energy consumption, can significantly reduce gas separation energy consumption and is gradually replacing traditional high-energy-consumption separation processes, demonstrating broad application prospects and development potential.

[0003] Robeson, an expert in separation membrane research, pointed out through systematic research that in gas separation processes, there is a trade-off relationship between the gas flux and selectivity of polymer membranes for specific gas pairs. That is, high gas flux is often accompanied by low selectivity, which is not conducive to achieving efficient separation (see reference). Journal of Membrane Science ,1991, 62, 165-185; Journal of Membrane Science (2008, 320, 390-400.). To overcome this limitation, researchers Budd and McKeown et al. introduced functional building blocks with rigid twisted structures into the polymer backbone, developing self-porous polymer (PIM) membranes (see reference). Advanced Materials , 2004, 16, 456-459.). The twisted molecular chain structure of this type of material effectively suppresses the close packing between chain segments, forming internally connected and irregularly shaped free volume units ( ). FVE These units are similar in nature to micropores with a size of less than 2 nanometers, which significantly improves the gas separation performance of the material and breaks through the bottleneck problem of flux and selectivity being mutually constrained by traditional separation membranes.

[0004] Polyimide (PI) possesses excellent comprehensive physical properties and can withstand complex operating conditions such as high pressure and high temperature, attracting significant attention in the field of gas separation membranes in recent years. Researchers have introduced a large-volume, rigid twisted structure into the PI backbone to develop self-polymerizing microporous polyimide (PIM-PI) separation membranes, which exhibit superior gas separation performance. Tröger's Base (TB) motifs, as rigid twisted motifs with a "V-shaped" bridging structure, can serve as rigid twisting sites in self-porous polymers. Fluorenyl Cardo structures, with their large side groups and high rigidity, are beneficial for reducing close packing between molecular chains and increasing micropore and ultramicropore structures. Therefore, introducing TB motifs in conjunction with fluorenyl Cardo structures into the PI molecular chain is expected to simultaneously improve the gas permeability and selectivity of the membrane, overcoming the technical bottleneck of the mutual constraint between gas permeability and selectivity in this field, and providing new possibilities for the preparation of high-performance gas separation membranes.

[0005] Currently, polymer gas separation membranes not only face the long-standing problem of the "trade-off" effect, making it difficult to simultaneously achieve gas permeability and selectivity, thus limiting the overall separation efficiency of the membrane, but also suffer from low polymerization activity and difficulty in obtaining high molecular weight polymers due to the significant steric hindrance of both Cardo dianhydrides with large rigid side groups and TB diamines with twisted structures. This results in poor polymer film-forming properties, inconspicuous pore structure, and insufficient mechanical properties, failing to meet practical separation applications. Conventional highly reactive aromatic diamines (such as p-phenylenediamine or m-phenylenediamine) still cannot fully compensate for their low reactivity when copolymerizing with the aforementioned sterically hindered monomers, or although they can increase the molecular weight, they cannot achieve subsequent "thermal-oxidative crosslinking." Furthermore, although it is known that high-temperature treatment in an air atmosphere can improve selectivity by inducing crosslinking through free radicals generated by alkyl substituents, this general method suffers from poor process adaptability, unclear control rules, and difficulty in achieving an optimal trade-off between permeability and selectivity when applied to the specific Cardo / TB copolymer system of this invention. Summary of the Invention

[0006] To address the aforementioned problems, this invention provides a polyimide gas separation membrane comprising both a fluorene-based Cardo structure and a Tröger's Base (TB) moiety, and a method for preparing the same.

[0007] First, the present invention provides a polyimide gas separation membrane comprising both a fluorene-based Cardo structure and a Tröger's Base (TB) moiety. The gas separation membrane is prepared by thermal-oxidative crosslinking of a gas separation membrane precursor comprising a polyimide of formula (I). The polyimide of formula (I) has the following structure:

[0008] (I) Wherein, A is a dicarboxylic acid anhydride residue containing a fluorenyl Cardo structure, with a molar fraction of 50%; B is a diamine residue containing a TB moiety, with a molar fraction of 5% to 30%; C is an aromatic diamine residue containing a short-chain alkyl substituent, with a molar fraction of 45% to 20%, and m:n = 0.11-1.5.

[0009] Furthermore, the dicarboxylic anhydride containing the fluorenyl Cardo structure is any one or a combination of the following compounds, whose chemical structural formula is:

[0010] Where X = O, S, NH, ester bond, thioester bond or amide bond.

[0011] Furthermore, the diamine containing TB is any one or a combination of the following compounds, with the following chemical structural formulas: .

[0012] Furthermore, the aromatic diamine containing short-chain alkyl substituents is any one or a combination of the following compounds, with the following chemical structural formulas: .

[0013] The present invention also provides a method for preparing a polyimide gas separation membrane comprising both a fluorene-based Cardo structure and a Tröger's Base (TB) moiety as described above, the method comprising the following steps: Step 1: The diacid anhydride A containing a fluorenyl Cardo structure, the diamine B containing a TB moiety, and the aromatic diamine C containing a short-chain alkyl substituent are vacuum-treated at 80-150 °C for 6-12 h; the definitions of the diacid anhydride A, diamine B, and aromatic diamine C are as described above; Step 2: Under the protection of an inert gas, add the diacid anhydride A, diamine B, aromatic diamine C, catalyst D and high-boiling solvent E treated in Step 1 into the reactor in sequence, stir and heat the reaction system to 50~100 ℃, and stir for 3~8 h. The total mass fraction of the dicarboxylic acid anhydride A, diamine B, and aromatic diamine C in the reaction system is 10 wt% to 30 wt%. The molar ratio of the dicarboxylic acid anhydride A, diamine B, and aromatic diamine C is 1~1.05: x :(1- x ),in x The value range is 0.1 to 0.6; The molar ratio of the dicarboxylic acid anhydride A to the catalyst D is 1:1.5~4.0; Step 3: Under inert gas protection, add catalyst F and compatibilizer G to the reaction system in step 2, heat the reaction system to 120~220 ℃, and continue stirring the reaction for 8~16 h; The amount of catalyst F is 5 wt% to 10 wt% of the mass of diacid anhydride A added; The compatibilizer G is used in an amount of 30 wt% to 300 wt% of the added mass of dicarboxylic anhydride A. Step 4: When the system is cooled to 15~35 ℃, the reaction solution is poured into alcohol H to precipitate fibrous solid product. The product is filtered and the filter cake is washed with alcohol H. Then the filter cake is extracted with alcohol H for 8~24 h. Finally, the filter cake is vacuum dried at 80~160 ℃ for 12~24 h to obtain polymer I. Step 5: Dissolve polymer I in solvent J, with the solid content controlled at 0.5 wt%~15 wt%, filter, and then pour onto a clean glass plate that has been pre-leveled; place the glass plate in a vacuum oven at 25~80 ℃ to evaporate the solvent for 10~72 h, then raise the temperature to 80~160 ℃ and vacuum dry for 6~12 h; after the temperature drops to 20~35 ℃, remove the film to obtain the gas separation membrane precursor; Step 6: Place the gas separation membrane precursor in a tubular furnace equipped with a gas flow meter and an oxygen concentration sensor. Continuously purge the tubular furnace with an oxygen / nitrogen mixture for 10-30 min to stabilize the oxygen concentration (volume fraction) in the tubular furnace at a certain value. Close the gas flow valve and raise the temperature of the tubular furnace to 120-220 ℃ at a rate of 1-10 ℃ / min, hold for 0.5-3 h, and then raise the temperature to 300-450 ℃ at a rate of 1-10 ℃ / min, hold for 0.5-5 h. After the temperature drops to 20-35 ℃, remove the film to obtain the thermo-oxygen crosslinked Cardo-TB-PI-TC gas separation membrane material, which is a polyimide gas separation membrane that simultaneously contains fluorene Cardo structure and Tröger's Base (TB) unit.

[0014] Furthermore, in the method for preparing the polyimide gas separation membrane that simultaneously contains a fluorenyl Cardo structure and a Tröger's Base (TB) moiety, in step 2, the catalyst D is any one or a combination of benzoic acid, terephthalic acid, isophthalic acid, phthalic acid, p-methylbenzoic acid, m-methylbenzoic acid, o-methylbenzoic acid, p-ethylbenzoic acid, m-ethylbenzoic acid, o-ethylbenzoic acid, p-isopropylbenzoic acid, m-isopropylbenzoic acid, o-isopropylbenzoic acid, p-hydroxybenzoic acid, m-hydroxybenzoic acid, o-hydroxybenzoic acid, naphtholic acid, 4-phenylbenzoic acid, and 3-phenylbenzoic acid; The high-boiling-point solvent E is any one or a combination of phenol, p-cresol, m-cresol, o-cresol, p-ethylphenol, m-ethylphenol, o-ethylphenol, 2,4-dimethylphenol, 2,3-dimethylphenol, 2,6-dimethylphenol, 2,5-dimethylphenol, 3,5-dimethylphenol, and 3,4-dimethylphenol.

[0015] Furthermore, in the method for preparing the polyimide gas separation membrane that simultaneously contains a fluorenyl Cardo structure and a Tröger's Base (TB) moiety, in step 3, the catalyst F is any one or a combination of tert-butylpyridine, quinoline, 6-methylquinoline, 4-methylquinoline, isoquinoline, and 8-methylisoquinoline.

[0016] The compatibilizer G is any one or a combination of calcium chloride, lithium chloride, and lithium bromide. Furthermore, in the method for preparing the polyimide gas separation membrane that simultaneously contains a fluorenyl Cardo structure and a Tröger's Base (TB) moiety, in step 4, the alcohol H is any one of methanol, ethanol, isopropanol, or a combination thereof.

[0017] Furthermore, in the method for preparing the polyimide gas separation membrane that simultaneously contains a fluorenyl Cardo structure and a Tröger's Base (TB) moiety, in step 5, the solvent J is any one or a combination of chloroform, dichloromethane, tetrahydrofuran, dioxane, acetonitrile, ethyl acetate, acetone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and γ-butyrolactone.

[0018] Furthermore, in the method for preparing the polyimide gas separation membrane that simultaneously contains fluorene-based Cardo structures and Tröger's Base (TB) units, in step 6, after purging the tube furnace with an oxygen / nitrogen mixed gas flow, the oxygen volume fraction inside the tube furnace is stabilized at 0.1%~10%.

[0019] Beneficial effects This invention, from the perspective of molecular structure design, develops a technique for introducing a fluorenyl Cardo structure, a TB moiety, and short-chain alkyl substituents into the main chain of a polyimide (PI) molecule. Utilizing the thermo-oxidative crosslinking reaction of alkyl groups under aerobic conditions, the interchain stacking state and membrane pore structure are further optimized, significantly improving the overall gas separation performance of the PI membrane and exceeding the Robeson limit. The PI gas separation membrane prepared by this invention possesses advantages such as high permeation flux, high selectivity, high strength, and resistance to plasticization. The technical route proposed in this invention can provide diverse design ideas for the molecular structure design, efficient preparation, and separation performance optimization of PI gas separation membranes, contributing to the widespread application of PI gas separation membranes in the field of separation and purification.

[0020] This invention achieves precise control over the free volume and pore structure of the heat-treated separation membrane through fine optimization of the post-processing technology. The ultimate goal is to significantly improve gas selectivity by moderately sacrificing gas permeation flux within an acceptable range, thereby optimizing the overall separation performance and providing an effective technical means to break through the "trade-off" balance. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the thermo-oxidative crosslinking mechanism; Figure 2 Here are photographs of the gas separation membrane precursors prepared in several examples: (a) Example 8, (b) Example 9, (c) Example 10; Figure 3 These are photographs of the gas separation membrane after thermo-oxidative crosslinking: (a) Example 11, (b) Example 12; Figure 4 The thermal properties of the gas separation membrane precursors prepared in Examples 8, 9, and 10 are shown: (a) TGA curve, (b) curve of internal friction factor tan δ as a function of temperature. Figure 5 The nitrogen adsorption performance data of the precursor polymers prepared in Examples 8, 9, and 10 are as follows: (a) adsorption-desorption curves, (b) pore size distribution. Figure 6 This is a comparison chart of the CO2 / CH4 separation performance of the precursor gas separation membranes prepared in Examples 2 and 3 with the Robeson upper limit; Figure 7 (a) is a comparison chart of the CO2 / CH4 separation performance of the precursor films and the films after thermo-oxidative crosslinking prepared in Examples 4 and 5 with the upper limit of Robeson's algorithm; (b) is a comparison chart of the CO2 / CH4 separation performance of the precursor films and the films after thermo-oxidative crosslinking prepared in Examples 6 and 7 with the upper limit of Robeson's algorithm. Figure 8 The plasticization resistance of the precursor films prepared in Examples 11 and 12 and the films after thermo-oxidative crosslinking is shown. Figure 9 This is a comparison chart of the CO2 / CH4 separation performance of the films prepared in Examples 8, 9, and 10 after undergoing thermo-oxidative crosslinking, and the upper limit of Robeson's algorithm. Detailed Implementation

[0022] The present invention is described in detail through the following embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection of the present invention.

[0023] Example 1 As a comparative example, this embodiment provides a method for preparing a polyimide containing Cardo 5 and TBDA 3, wherein Cardo 5 and TBDA 3 have the following structures respectively: , ; Specifically, the following steps are included: 2.06 g of Cardo 5 and 1.12 g of TBDA 3 were vacuum-treated at 80 °C for 12 h. After cooling to room temperature, they were added sequentially to a 100 mL three-necked flask under argon protection, along with 1.66 g of terephthalic acid and 7.5 g of p-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.14 g of 6-methylquinoline and 3.0 g of calcium chloride were added, and the reaction system was heated to 200 °C and stirred for another 16 h. When the system cooled to 35 °C, it was poured into ethanol to precipitate a powdery solid product. The product was filtered, and the filter cake was washed three times with ethanol. The filter cake was then extracted with ethanol for 12 h, and finally dried under vacuum at 80 °C for 12 h to obtain 2.9 g (91% yield) of polymer. 0.6 g of the polymer was dissolved in 11.4 g of chloroform (5 w.t.% solids), filtered, and dripped onto a clean, leveled glass plate. The glass plate was placed in a vacuum oven at 30 °C to evaporate the solvent for 18 h, then the temperature was raised to 80 °C and vacuum dried for 6 h. After the temperature dropped to 25 °C, film formation failed, and only film fragments were obtained. The weight-average molecular weight of the prepared polymer (…) M w See Table 1.

[0024] Example 2 As a comparative example, this embodiment provides a method for preparing a polyimide containing Cardo 7 and TBDA 2, wherein Cardo 7 and TBDA 2 have the following structures: , ; Specifically, the following steps are included: 2.44 g Cardo 7, 0.45 g TBDA 2, and 0.26 g p-phenylenediamine were treated under vacuum at 90 °C for 10 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.63 g p-methylbenzoic acid and 10 g o-cresol. The reaction system was stirred and heated to 80 °C for 4 h. Subsequently, 0.17 g quinoline and 4.0 g lithium bromide were added, and the reaction system was heated to 180 °C and stirred for another 14 h. When the system cooled to 35 °C, the reaction solution was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed four times with methanol. The filter cake was then extracted with methanol for 10 h, and finally dried under vacuum at 100 °C for 12 h to obtain 3.09 g (98% yield) of polymer. 0.6 g of polymer was dissolved in 20 g of chloroform (solid content 2.9 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 25 ℃ to evaporate the solvent for 16 h, then the temperature was raised to 80 ℃ for vacuum drying for 8 h. After the temperature dropped to 25 ℃, the film was removed to obtain the gas separation membrane precursor. The weight-average molecular weight of the prepared polymer (…) M w See Table 1. Mechanical property test results show that the precursor film has poor mechanical properties (see Table 1). The CO2 / CH4 gas separation performance of the precursor film is as follows: Figure 6 As shown, the overall gas separation performance is not ideal and does not exceed the 1991 Robeson separation limit.

[0025] Example 3 As a comparative example, this embodiment provides a method for preparing a polyimide containing Cardo 4 and TBDA 5, wherein Cardo 4 and TBDA 5 have the following structures: , ; Specifically, the following steps are included: 1.95 g Cardo 4, 0.49 g TBDA 5, and 0.26 g m-phenylenediamine were treated under vacuum at 80 °C for 10 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.09 g o-methylbenzoic acid and 11 g m-cresol. The reaction system was stirred and heated to 60 °C for 7 h. Subsequently, 0.17 g isoquinoline and 1.2 g lithium bromide were added, and the reaction system was heated to 180 °C and stirred for another 12 h. When the system cooled to 25 °C, the reaction solution was poured into ethanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with ethanol. The filter cake was then extracted with ethanol for 12 h, and finally dried under vacuum at 120 °C for 16 h to obtain 2.57 g (95% yield) of polymer. 0.6 g of polymer was dissolved in 9.4 g of N,N-dimethylformamide (solid content 6.0 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 °C to evaporate the solvent for 48 h, then the temperature was raised to 120 °C and vacuum dried for 8 h. After the temperature dropped to 25 °C, the film was removed to obtain the gas separation membrane precursor. The weight-average molecular weight of the prepared polymer (…) M w (See Table 1.) The mechanical property test results show that the precursor film has poor mechanical properties. The CO2 / CH4 gas separation performance of the precursor film is as follows: Figure 6 As shown, the overall gas separation performance is not ideal and does not exceed the 1991 Robeson separation limit.

[0026] Table 1

[0027] The above comparative experiments confirm that using unsubstituted p-phenylenediamine or m-phenylenediamine results in a lower molecular weight polymer after copolymerization, leading to poor gas separation performance and overall physical properties.

[0028] Example 4 In comparison, this embodiment provides a method for preparing a polyimide comprising Cardo 4, TBDA 1, and diamine 2, wherein Cardo 4, TBDA 1, and diamine 2 each have the following structures: , , ; Specifically, the following steps are included: 1.95 g of diacid anhydride Cardo 4, 0.40 g of TBDA 1, and 0.33 g of diamine 2 were treated under vacuum at 80 °C for 6 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.63 g of m-methylbenzoic acid and 10 g of p-ethylphenol. The reaction system was stirred and heated to 90 °C for 6 h. Subsequently, 0.13 g of 4-methylquinoline and 2.5 g of calcium chloride were added, and the reaction system was heated to 180 °C and stirred for another 12 h. When the system cooled to 35 °C, it was poured into methanol to obtain a fibrous solid product. The product was filtered, and the filter cake was washed three times with methanol. The filter cake was then extracted with methanol for 12 h, and finally dried under vacuum at 80 °C for 16 h to obtain 2.55 g (95% yield) of polymer. 0.6 g of polymer was dissolved in 9.4 g of N,N-dimethylacetamide (solid content 6.0 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 6 h. After the temperature dropped to 25 ℃, the film was removed to obtain the gas separation membrane precursor. The gas separation membrane precursor was placed in a tube furnace equipped with a gas flow meter and an oxygen concentration sensor. The tube furnace was continuously purged with compressed air at a flow rate of 100 mL / min for 20 min. Then, the tube furnace was heated to a specific temperature at a heating rate of 5 ℃ / min in an air flow rate of 100 mL / min and held at that temperature for a certain time to complete the thermo-oxidative crosslinking. The precursor films prepared in this embodiment were tested using three thermo-oxidative crosslinking processes reported in the literature (crosslinking temperature: 300 ℃, holding time 10 h; crosslinking temperature: 370 ℃, holding time 1 h; crosslinking temperature: 390 ℃, holding time 10 min). After the temperature dropped to 25 ℃, the films were removed, yielding three different thermo-oxidative crosslinked gas separation membrane materials. The CO2 / CH4 gas separation performance of the films before and after thermo-oxidative crosslinking is as follows: Figure 7 As shown in (a), the permeability of the membrane to CO2 decreased significantly after thermo-oxidative crosslinking, the selectivity of the CO2 / CH4 gas pair only increased slightly, the overall gas separation performance deteriorated, and the separation performance was far from the Robeson upper limit in 1991.

[0029] Example 5 In comparison, this embodiment provides a method for preparing a polyimide comprising Cardo 2, TBDA 4, and diamine 3, wherein Cardo 2, TBDA 4, and diamine 3 each have the following structures: , , ; Specifically, the following steps are included: 2.70 g of Cardo 2 (substituent X=S), 0.37 g of TBDA 4, and 0.42 g of diamine 3 were treated under vacuum at 80 °C for 8 h. After cooling to room temperature, they were added sequentially to a 100 mL three-necked flask under argon protection, along with 1.2 g of p-ethylbenzoic acid and 14 g of m-cresol. The reaction system was stirred and heated to 80 °C for 4 h. Subsequently, 0.16 g of tert-butylpyridine and 5.5 g of lithium bromide were added, and the reaction system was heated to 180 °C and stirred for another 12 h. When the system cooled to 25 °C, the reaction solution was poured into isopropanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with isopropanol. The filter cake was then extracted with isopropanol for 12 h. Finally, the filter cake was dried under vacuum at 120 °C for 12 h to obtain 3.39 g (97% yield) of polymer. 0.6 g of polymer was dissolved in 7.0 g of N,N-dimethylacetamide (solid content 7.89 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 80 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 12 h. After the temperature dropped to 25 ℃, the film was removed to obtain the gas separation membrane precursor. The gas separation membrane precursor was placed in a tube furnace equipped with a gas flow meter and an oxygen concentration sensor. The tube furnace was continuously purged with compressed air at a flow rate of 100 mL / min for 20 min. Then, the tube furnace was heated to a specific temperature at a heating rate of 5 ℃ / min in an air flow rate of 100 mL / min and held at that temperature for a certain time to complete the thermo-oxidative crosslinking. The precursor films prepared in this embodiment were tested using three thermo-oxidative crosslinking processes reported in the literature (crosslinking temperature: 300℃, holding time 10 h; crosslinking temperature: 370℃, holding time 1 h; crosslinking temperature: 390℃, holding time 10 min). After the temperature dropped to 25℃, the films were removed, yielding three different thermo-oxidative crosslinked gas separation membrane materials. The CO2 / CH4 gas separation performance of the films before and after thermo-oxidative crosslinking is as follows: Figure 7 As shown in (a), the permeability of the membrane to CO2 decreased significantly after thermo-oxidative crosslinking, the selectivity of the CO2 / CH4 gas pair only increased slightly, the overall gas separation performance deteriorated, and the separation performance was far from the Robeson upper limit in 1991.

[0030] Example 6 In comparison, this embodiment provides a method for preparing a polyimide comprising Cardo 3, TBDA 8, and diamine 11, wherein Cardo 3, TBDA 8, and diamine 11 each have the following structures: , , ; Specifically, the following steps are included: 2.57 g of Cardo 3 (substituent X=O), 0.37 g of TBDA 8, and 0.50 g of diamine 11 were treated under vacuum at 85°C for 6 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.09 g of p-methylbenzoic acid and 13 g of 2,4-dimethylphenol. The reaction system was stirred and heated to 80°C for 4 h. Subsequently, 0.16 g of quinoline and 6.0 g of lithium bromide were added, and the reaction system was heated to 180°C and stirred for another 12 h. When the system cooled to 25°C, the reaction solution was poured into ethanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with ethanol. The filter cake was then extracted with ethanol for 10 h, and finally dried under vacuum at 80°C for 16 h to obtain 3.30 g (96% yield) of polymer. 0.6 g of polymer was dissolved in 40 g of chloroform (solid content 1.48 wt%), filtered, and then poured onto a clean, leveled glass plate. The glass plate was placed in a vacuum oven at 30 ℃ to evaporate the solvent for 20 h, and then the temperature was raised to 100 ℃ for vacuum drying for 12 h. After the temperature dropped to 25 ℃, the film was removed to obtain the gas separation membrane precursor. The gas separation membrane precursor was placed in a tube furnace equipped with a gas flow meter and an oxygen concentration sensor, and the tube furnace was continuously purged with an oxygen / nitrogen mixture for 20 min to stabilize the oxygen concentration (volume fraction) in the tube furnace at 18%. The gas flow valve was closed, and the temperature of the tube furnace was increased to 160 ℃ at a rate of 3.0 ℃ / min and held for 1.0 h. Then, the temperature was increased to 350 ℃ at a rate of 3.0 ℃ / min and held for 1.0 h. After the temperature dropped to 25 ℃, the film was removed to obtain the thermo-oxygen crosslinked Cardo-TB-PI-TC-6 gas separation membrane material. CO2 / CH4 gas separation performance of the film before and after thermo-oxidative crosslinking is as follows Figure 7 As shown in (b), the membrane shrinks after thermo-oxidative crosslinking, the CO2 permeability decreases significantly, the selectivity of the CO2 / CH4 gas pair only slightly improves, the overall gas separation performance deteriorates, and the separation performance is far from the 1991 Robeson upper limit.

[0031] Example 7 This embodiment provides a method for preparing a polyimide comprising Cardo 3, TBDA 8, and diamine 11, wherein the structures of Cardo 3, TBDA 8, and diamine 11 are as described in Example 6, and specifically includes the following steps: 2.57 g of Cardo 3 (substituent X=O), 0.37 g of TBDA 8, and 0.50 g of diamine 11 were treated under vacuum at 85°C for 6 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.09 g of p-methylbenzoic acid and 13 g of 2,4-dimethylphenol. The reaction system was stirred and heated to 80°C for 4 h. Subsequently, 0.16 g of quinoline and 6.0 g of lithium bromide were added, and the reaction system was heated to 180°C and stirred for another 12 h. When the system cooled to 25°C, the reaction solution was poured into ethanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with ethanol. The filter cake was then extracted with ethanol for 10 h, and finally dried under vacuum at 80°C for 16 h to obtain 3.30 g (96% yield) of polymer. 0.6 g of polymer was dissolved in 40 g of chloroform (solid content 1.48 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 30 ℃ to evaporate the solvent for 20 h, and then the temperature was raised to 100 ℃ for vacuum drying for 12 h. After the temperature dropped to 25 ℃, the film was removed to obtain the gas separation membrane precursor. The gas separation membrane precursor was placed in a tube furnace equipped with a gas flow meter and an oxygen concentration sensor, and the tube furnace was continuously purged with an oxygen / nitrogen mixture for 20 min to stabilize the oxygen concentration (volume fraction) in the tube furnace at 10%. The gas flow valve was closed, and the temperature of the tube furnace was increased to 160 ℃ at a rate of 3.0 ℃ / min and held for 1.0 h. Then, the temperature was increased to 350 ℃ at a rate of 3.0 ℃ / min and held for 1.0 h. After the temperature dropped to 25 ℃, the film was removed to obtain the thermo-oxygen crosslinked Cardo-TB-PI-TC-7 gas separation membrane material. CO2 / CH4 gas separation performance of the film before and after thermo-oxidative crosslinking is as follows Figure 7 As shown in (b), the membrane did not shrink significantly after thermo-oxidative crosslinking. Although the permeability to CO2 decreased, the selectivity for CO2 / CH4 gas pairs was significantly improved, and the overall gas separation performance was significantly improved, exceeding the Robeson limit set in 1991.

[0032] Example 8 This embodiment provides a method for preparing a polyimide comprising Cardo 1, TBDA 2, and diamine 4, wherein Cardo 3, TBDA 8, and diamine 11 have the following structures: , , ; Specifically, the following steps are included: 2.56 g of Cardo 1 (substituent X = NH), 0.11 g of TBDA 2, and 0.59 g of diamine 4 were treated under vacuum at 80°C for 6 h. After cooling to room temperature, they were added sequentially to a 100 mL three-necked flask under argon protection, along with 1.22 g of benzoic acid and 11 g of m-cresol. The reaction system was stirred and heated to 90°C for 6 h. Subsequently, 0.14 g of isoquinoline and 4.0 g of lithium chloride were added, and the reaction system was heated to 180°C and stirred for another 10 h. When the system cooled to 25°C, the reaction solution was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed four times with methanol. The filter cake was then extracted with methanol for 16 h, and finally dried under vacuum at 80°C for 18 h to obtain 3.11 g (95% yield) of polymer. 0.6 g of polymer was dissolved in 40 g of chloroform (solid content 1.48 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 30 ℃ to evaporate the solvent for 36 h, and then the temperature was raised to 80 ℃ for vacuum drying for 6 h. After the temperature dropped to 25 ℃, the film was removed to obtain the gas separation membrane precursor. The gas separation membrane precursor was placed in a tube furnace equipped with a gas flow meter and an oxygen concentration sensor, and the tube furnace was continuously purged with an oxygen / nitrogen mixture for 30 min to stabilize the oxygen concentration (volume fraction) in the tube furnace at 1%. The gas flow valve was closed, and the temperature of the tube furnace was raised to 160 ℃ at a rate of 3 ℃ / min and held for 1 h. Then, the temperature was raised to 350 ℃ at a rate of 3 ℃ / min and held for 1 h. After the temperature dropped to 25 ℃, the film was removed to obtain the thermo-oxygen crosslinked Cardo-TB-PI-TC-8 gas separation membrane material. The CO2 / CH4 gas separation performance of the membrane after thermo-oxidative crosslinking is as follows: Figure 9 As shown.

[0033] Example 9 This embodiment provides a method for preparing a polyimide comprising Cardo 1, TBDA 2, and diamine 4, wherein the structures of Cardo 3, TBDA 8, and diamine 11 are as shown in Example 8, and specifically includes the following steps: 2.56 g of Cardo 1 (substituent X = NH), 0.28 g of TBDA 2, and 0.49 g of diamine 4 were treated under vacuum at 80°C for 6 h. After cooling to room temperature, they were added sequentially to a 100 mL three-necked flask under argon protection, along with 1.22 g of benzoic acid and 11 g of m-cresol. The reaction system was stirred and heated to 90°C for 6 h. Subsequently, 0.14 g of isoquinoline and 2.5 g of lithium chloride were added, and the reaction system was heated to 180°C and stirred for another 10 h. When the system cooled to 25°C, the reaction solution was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed four times with methanol. The filter cake was then extracted with methanol for 16 h, and finally dried under vacuum at 80°C for 18 h to obtain 3.24 g (97% yield) of polymer. 0.6 g of polymer was dissolved in 5.4 g of N,N-dimethylformamide (solid content 10 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 8 h. After the temperature dropped to 25 ℃, the film was removed to obtain the gas separation membrane precursor. The gas separation membrane precursor was placed in a tube furnace equipped with a gas flow meter and an oxygen concentration sensor, and the tube furnace was continuously purged with an oxygen / nitrogen mixture for 30 min to stabilize the oxygen concentration (volume fraction) in the tube furnace at 5%. The gas flow valve was closed, and the temperature of the tube furnace was raised to 160 ℃ at a rate of 3 ℃ / min and held for 1 h. Then, the temperature was raised to 350 ℃ at a rate of 3 ℃ / min and held for 1 h. After the temperature dropped to 25 ℃, the film was removed to obtain the thermo-oxygen crosslinked Cardo-TB-PI-TC-9 gas separation membrane material. The CO2 / CH4 gas separation performance of the membrane after thermo-oxidative crosslinking is as follows: Figure 9 As shown.

[0034] Example 10 This embodiment provides a method for preparing a polyimide comprising Cardo 1, TBDA 2, and diamine 4, wherein the structures of Cardo 3, TBDA 8, and diamine 11 are as shown in Example 8, and specifically includes the following steps: 2.56 g of Cardo 1 (substituent X = NH), 0.56 g of TBDA 2, and 0.33 g of diamine 4 were treated under vacuum at 80°C for 6 h. After cooling to room temperature, they were added sequentially to a 100 mL three-necked flask under argon protection, along with 1.22 g of benzoic acid and 11 g of m-cresol. The reaction system was stirred and heated to 90°C for 6 h. Subsequently, 0.14 g of isoquinoline and 1.0 g of lithium chloride were added, and the reaction system was heated to 180°C and stirred for another 10 h. When the system cooled to 25°C, the reaction solution was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed four times with methanol. The filter cake was then extracted with methanol for 16 h, and finally dried under vacuum at 80°C for 18 h to obtain 3.38 g (98% yield) of polymer. 0.6 g of polymer was dissolved in 5.4 g of N,N-dimethylformamide (solid content 10 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 8 h. After the temperature dropped to 25 ℃, the film was removed to obtain the gas separation membrane precursor. The gas separation membrane precursor was placed in a tube furnace equipped with a gas flow meter and an oxygen concentration sensor, and the tube furnace was continuously purged with an oxygen / nitrogen mixture for 30 min to stabilize the oxygen concentration (volume fraction) in the tube furnace at 8%. The gas flow valve was closed, and the temperature of the tube furnace was raised to 160 ℃ at a rate of 3 ℃ / min and held for 1 h. Then, the temperature was raised to 350 ℃ at a rate of 3 ℃ / min and held for 1 h. After the temperature dropped to 25 ℃, the film was removed to obtain the thermo-oxygen crosslinked Cardo-TB-PI-TC-10 gas separation membrane material. The CO2 / CH4 gas separation performance of the membrane after thermo-oxidative crosslinking is as follows: Figure 9 As shown.

[0035] Example 11 This embodiment provides a method for preparing a polyimide comprising Cardo 5, TBDA 7, and diamine 17, wherein Cardo 5, TBDA 7, and diamine 17 each have the following structures: , , ; Specifically, the following steps are included: 2.06 g Cardo 5, 0.45 g TBDA 7, and 0.58 g diamine 17 were vacuum-treated at 80 °C for 6 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.66 g p-hydroxybenzoic acid and 18 g p-cresol. The reaction system was stirred and heated to 80 °C for 4 h. Subsequently, 0.13 g quinoline and 2.0 g lithium bromide were added, and the reaction system was heated to 200 °C and stirred for another 12 h. When the system cooled to 35 °C, it was poured into ethanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with ethanol. The filter cake was then extracted with ethanol for 12 h, and finally dried under vacuum at 120 °C for 16 h to obtain 2.96 g (96% yield) of polymer. 0.6 g of polymer was dissolved in 30 g of chloroform (solid content 1.96 wt%), filtered, and then poured onto a clean, leveled glass plate. The glass plate was placed in a vacuum oven at 30 ℃ to evaporate the solvent for 16 h, and then the temperature was raised to 80 ℃ for vacuum drying for 6 h. After the temperature dropped to 25 ℃, the film was removed to obtain the gas separation membrane precursor. The gas separation membrane precursor was placed in a tube furnace equipped with a gas flow meter and an oxygen concentration sensor. The tube furnace was continuously purged with an oxygen / nitrogen mixture for 20 min to stabilize the oxygen concentration (volume fraction) in the tube furnace at 10%. The gas flow valve was closed, and the temperature of the tube furnace was increased to 160 ℃ at a rate of 3 ℃ / min and held for 1 h. Then, the temperature was increased to 350 ℃ at a rate of 3 ℃ / min and held for 0.5 h. After the temperature dropped to 25 ℃, the film was removed to obtain the thermo-oxygen crosslinked Cardo-TB-PI-TC-11 gas separation membrane material.

[0036] Example 12 This embodiment provides a method for preparing a polyimide comprising Cardo 5, TBDA 7, and diamine 17, wherein the structures of Cardo 5, TBDA 7, and diamine 17 are as shown in Example 11, and specifically includes the following steps: 2.06 g Cardo 5, 0.45 g TBDA 7, and 0.58 g diamine 17 were vacuum-treated at 80 °C for 6 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.66 g p-hydroxybenzoic acid and 18 g p-cresol. The reaction system was stirred and heated to 80 °C for 4 h. Subsequently, 0.13 g quinoline and 2.0 g lithium bromide were added, and the reaction system was heated to 200 °C and stirred for another 12 h. When the system cooled to 35 °C, it was poured into ethanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with ethanol. The filter cake was then extracted with ethanol for 12 h, and finally dried under vacuum at 120 °C for 16 h to obtain 2.96 g (96% yield) of polymer. 0.6 g of polymer was dissolved in 30 g of chloroform (solid content 1.96 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 30 ℃ to evaporate the solvent for 16 h, and then the temperature was raised to 80 ℃ for vacuum drying for 6 h. After the temperature dropped to 25 ℃, the film was removed to obtain the gas separation membrane precursor. The gas separation membrane precursor was placed in a tube furnace equipped with a gas flow meter and an oxygen concentration sensor. The tube furnace was continuously purged with an oxygen / nitrogen mixture for 20 min to stabilize the oxygen concentration (volume fraction) in the tube furnace at 10%. The gas flow valve was closed, and the temperature of the tube furnace was increased to 160 ℃ at a rate of 3 ℃ / min and held for 1 h. Then, the temperature was increased to 350 ℃ at a rate of 3 ℃ / min and held for 1 h. After the temperature dropped to 25 ℃, the film was removed to obtain the thermo-oxygen crosslinked Cardo-TB-PI-TC-12 gas separation membrane material.

[0037] Experimental results show that the thermal decomposition temperature of the PI precursor film prepared in the embodiments of the present invention is above 500 °C (Example 9), and the glass transition temperature is above 400 °C (Example 10). After thermo-oxidative crosslinking, the permeability coefficients of the film for CO2 and CH4 are respectively... P (CO2) = 70.0 barrer, P (CH4) = 0.8 barrer, the ideal selectivity for CO2 / CH4 gas pairs can reach α (CO2 / CH4) = 87.5, exceeding the Robeson limit in 2008 (Example 8), and the film after thermo-oxidative crosslinking did not plasticize under a high-pressure CO2 environment of 30 bar, showing good resistance to plasticization (Examples 11, Example 12).

[0038] Examples 1-3 serve as a comparison. The polymers obtained by directly polymerizing anhydrides containing Cardo moiety with diamines containing TB moiety, and by copolymerizing unsubstituted p-phenylenediamine or m-phenylenediamine, had low molecular weights, resulting in poor gas separation performance and overall physical properties, and even failure to form films. In contrast, the embodiments of this invention introduce another highly reactive aromatic diamine containing short-chain alkyl substituents during the polymerization process. This increases the molecular weight of the PI, and the alkyl substituents (methyl, ethyl, isopropyl) in the aromatic diamine provide "crosslinking sites" for subsequent thermo-oxidative crosslinking. In particular, the use of aromatic diamines with methyl or ethyl groups at the amino-ortho position has unique advantages in improving polymerization activity and pore formation: firstly, the electron-donating effect of methyl / ethyl enhances the reactivity of the diamine, which is beneficial for obtaining high molecular weights; secondly, the methyl / ethyl groups at the amino-ortho position can effectively restrict internal rotation of single bonds, increasing chain rigidity and facilitating the formation of more microporous structures.

[0039] Examples 4-6 are used for comparison. In Examples 4 and 5, the existing post-treatment process (air flow rate 100 mL / min) was directly applied to the copolymerization system of this invention. This not only caused severe shrinkage of the film under high temperature conditions but also significantly reduced the gas permeability of the separation membrane, with only a slight improvement in selectivity, resulting in the overall gas separation performance being far from the Robeson upper limit. Similarly, the excessively high oxygen concentration in the post-treatment of Example 6 also adversely affected the gas separation performance. This invention systematically redeveloped and optimized the "thermal-oxygen crosslinking" post-treatment process to maximize its compatibility with the system of this invention. Ultimately, it was determined that the best overall separation performance of the film was obtained when the oxygen volume concentration in the thermal-oxygen crosslinking atmosphere was 0.1%–10%. The fine optimization of the post-treatment process in this invention enables precise control of the free volume and pore structure of the heat-treated separation membrane. Within an acceptable range, it moderately sacrifices gas permeation flux to significantly improve gas selectivity, thereby optimizing the overall separation performance and providing an effective technical means to overcome the "trade-off" equilibrium.

Claims

1. A polyimide gas separation membrane comprising both a fluorene-based Cardo structure and a Tröger's Base (TB) moiety, characterized in that, The gas separation membrane is made by thermal-oxidative crosslinking of a gas separation membrane precursor comprising a polyimide of formula (I), wherein the polyimide of formula (I) has the following structure: (I) Wherein, A is a dicarboxylic acid anhydride residue containing a fluorenyl Cardo structure, with a molar fraction of 50%; B is a diamine residue containing a TB moiety, with a molar fraction of 5% to 30%; C is an aromatic diamine residue containing a short-chain alkyl substituent, with a molar fraction of 45% to 20%, and m:n = 0.11-1.

5.

2. The polyimide gas separation membrane according to claim 1, comprising both a fluorene-based Cardo structure and a Tröger's Base (TB) moiety, wherein the diacid anhydride comprising the fluorene-based Cardo structure is any one or a combination of the following compounds, with the chemical structural formula as follows: Where X = O, S, NH, ester bond, thioester bond or amide bond.

3. The polyimide gas separation membrane according to claim 1, comprising both a fluorene Cardo structure and a Tröger's Base (TB) moiety, wherein the diamine comprising the TB moiety is any one or a combination of the following compounds, with the chemical structural formula as follows: 。 4. The polyimide gas separation membrane according to claim 1, comprising both a fluorenyl Cardo structure and a Tröger's Base (TB) moiety, wherein the aromatic diamine comprising a short-chain alkyl substituent is any one or a combination of the following compounds, with the chemical structural formula as follows: 。 5. A method for preparing a polyimide gas separation membrane comprising both a fluorene-based Cardo structure and a Tröger's Base (TB) moiety as described in any one of claims 1-4, characterized in that, The preparation method includes the following steps: Step 1: Vacuum-treated diacid anhydride A containing a fluorenyl Cardo structure, diamine B containing a TB moiety, and aromatic diamine C containing a short-chain alkyl substituent at 80-150 °C for 6-12 h; the diacid anhydride A, diamine B, and aromatic diamine C are defined as described in any one of claims 1-4; Step 2: Under the protection of an inert gas, add the diacid anhydride A, diamine B, aromatic diamine C, catalyst D and high-boiling solvent E treated in Step 1 into the reactor in sequence, stir and heat the reaction system to 50~100 ℃, and stir for 3~8 h. The total mass fraction of the dicarboxylic acid anhydride A, diamine B, and aromatic diamine C in the reaction system is 10 wt%~30 w.t.%. The molar ratio of the dicarboxylic acid anhydride A, diamine B, and aromatic diamine C is 1~1.05: x :(1- x ),in x The value range is 0.1 to 0.6; The molar ratio of the dicarboxylic acid anhydride A to the catalyst D is 1:1.5~4.0; Step 3: Under inert gas protection, add catalyst F and compatibilizer G to the reaction system in step 2, heat the reaction system to 120~220 ℃, and continue stirring the reaction for 8~16 h; The amount of catalyst F is 5 wt% to 10 wt% of the mass of diacid anhydride A added; The compatibilizer G is used in an amount of 30 wt% to 300 wt% of the added mass of dicarboxylic anhydride A. Step 4: When the system is cooled to 15~35 ℃, the reaction solution is poured into alcohol H to precipitate fibrous solid product. The product is filtered and the filter cake is washed with alcohol H. Then the filter cake is extracted with alcohol H for 8~24 h. Finally, the filter cake is vacuum dried at 80~160 ℃ for 12~24 h to obtain polymer I. Step 5: Dissolve polymer I in solvent J, with the solid content controlled at 0.5 wt%~15 wt%, filter, and then pour onto a clean glass plate that has been pre-leveled; place the glass plate in a vacuum oven at 25~80 ℃ to evaporate the solvent for 10~72 h, then raise the temperature to 80~160 ℃ and vacuum dry for 6~12 h; after the temperature drops to 20~35 ℃, remove the film to obtain the gas separation membrane precursor; Step 6: Place the gas separation membrane precursor in a tubular furnace equipped with a gas flow meter and an oxygen concentration sensor. Continuously purge the tubular furnace with an oxygen / nitrogen mixture for 10-30 min to stabilize the oxygen concentration (volume fraction) within the furnace at a certain value. Close the gas flow valve and raise the temperature of the tubular furnace to 120-220 ℃ at a rate of 1-10 ℃ / min, holding for 0.5-3 h. Then raise the temperature to 300-450 ℃ at a rate of 1-10 ℃ / min, holding for 0.5-5 h. After the temperature drops to 20-35 ℃, remove the membrane to obtain the thermo-oxygen crosslinked Cardo-TB-PI-TC gas separation membrane material.

6. The method for preparing a polyimide gas separation membrane containing both a fluorenyl Cardo structure and a Tröger's Base (TB) moiety according to claim 5, wherein in step 2, the catalyst D is any one or a combination of benzoic acid, terephthalic acid, isophthalic acid, phthalic acid, p-methylbenzoic acid, m-methylbenzoic acid, o-methylbenzoic acid, p-ethylbenzoic acid, m-ethylbenzoic acid, o-ethylbenzoic acid, p-isopropylbenzoic acid, m-isopropylbenzoic acid, o-isopropylbenzoic acid, p-hydroxybenzoic acid, m-hydroxybenzoic acid, o-hydroxybenzoic acid, naphtholic acid, 4-phenylbenzoic acid, and 3-phenylbenzoic acid; The high-boiling-point solvent E is any one or a combination of phenol, p-cresol, m-cresol, o-cresol, p-ethylphenol, m-ethylphenol, o-ethylphenol, 2,4-dimethylphenol, 2,3-dimethylphenol, 2,6-dimethylphenol, 2,5-dimethylphenol, 3,5-dimethylphenol, and 3,4-dimethylphenol.

7. The method for preparing a polyimide gas separation membrane containing both a fluorenyl Cardo structure and a Tröger's Base (TB) moiety according to claim 5, wherein in step 3, the catalyst F is any one or a combination of tert-butylpyridine, quinoline, 6-methylquinoline, 4-methylquinoline, isoquinoline, and 8-methylisoquinoline; The compatibilizer G is any one of calcium chloride, lithium chloride, lithium bromide, or a combination thereof.

8. The method for preparing a polyimide gas separation membrane containing both a fluorenyl Cardo structure and a Tröger's Base (TB) moiety according to claim 5, wherein in step 4, the alcohol H is any one or a combination of methanol, ethanol, and isopropanol.

9. The method for preparing a polyimide gas separation membrane containing both a fluorenyl Cardo structure and a Tröger's Base (TB) moiety according to claim 5, wherein in step 5, the solvent J is any one or a combination of chloroform, dichloromethane, tetrahydrofuran, dioxane, acetonitrile, ethyl acetate, acetone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and γ-butyrolactone.

10. The method for preparing a polyimide gas separation membrane containing both fluorene-based Cardo structure and Tröger's Base (TB) moiety according to claim 5, wherein in step 6, after purging the tube furnace with an oxygen / nitrogen mixed gas flow, the oxygen volume fraction in the tube furnace is stabilized at 0.1%~10%.